The relationship between organizational climate and employee work loyalty in the X Department of West Sumatra Province - Rini Kandarvi; Herio Rizki Dewinda; Rany Fitriany; Risanita Fardian Farid (Psycho Holistic, 2024)
This research aims to determine the relationship between organizational climate and employee work loyalty at department X, West Sumatra Province. The measuring instruments used in this research are the organizational climate and work loyalty scales. The sampling used a saturated sampling technique with a sample size of 145 employees of department X of West Sumatra Province. The index discrimination item and reliability tests of both instruments showed that they were good (organizational climate scale 0,329 < rix < 0,842; α = 0,927, while the work loyalty scale 0,338 < rix < 0,760; α = 0,932). The hypothesis test in this research uses the Pearson Product Moment correlation with result analysis value of 0,752 (p < 0,001) meaning there is a significant correlation between organizational climate and employee work loyalty at department X, West Sumatra Province, where the direction of the correlation between the two variables is positive, show that if employee has a high organizational climate, then the employee will have high work loyalty, and conversely, if an employee has a low organizational environment, then the employee will have low work loyalty.